2015
DOI: 10.1007/s10526-015-9673-4
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of red rot disease by Bacillus sp. based biopesticide formulated in non-sterilized sugarcane filter cake

Abstract: Red rot disease affects sugarcane production adversely throughout the world. Intensive cropping and uninterrupted use of chemicals results in evolution of new pathotypes which can infect the resistant cultivars. Bacillus sp. inhabiting plant rhizosphere can protect the plants from multiple pathogens. In the present study, two antagonistic strains Bacillus subtilis NH-100 and Bacillus sp. NH-217 were able to maintain their population at 9.0 log CFU g -1 in sugarcane filter cake until nine months. These strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Liu et al (2010) demonstrated better control of S. sclerotiorum by cell-free filtrate of endophytic bacteria Yc8 application on the rapeseed leaves 24 h before fungal inoculation. Under field conditions, Bacillus isolate has a potential to be used as biobacteriocide in tomato plants (Santiago et al 2015) and for the control of red rot in sugarcane (Hassan et al 2015). However, the presence of biologically active metabolite produced by the antagonist, which diffused in the agar media, can be indicated by the zone of inhibition seen in the dual culture plates.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (2010) demonstrated better control of S. sclerotiorum by cell-free filtrate of endophytic bacteria Yc8 application on the rapeseed leaves 24 h before fungal inoculation. Under field conditions, Bacillus isolate has a potential to be used as biobacteriocide in tomato plants (Santiago et al 2015) and for the control of red rot in sugarcane (Hassan et al 2015). However, the presence of biologically active metabolite produced by the antagonist, which diffused in the agar media, can be indicated by the zone of inhibition seen in the dual culture plates.…”
Section: Discussionmentioning
confidence: 99%
“…The homogenate was centrifuged at 10,000 rpm, 4°C for 15 min and supernatant was used as crude enzyme extract [ 50 ]. Absorbance of PO, PPO and PAL, was observed on spectrophotometer at 280 nm, 450nm, 460 nm respectively [ 8 , 38 , 51 54 ]. Enzyme activity was expressed as change in absorbance min/ g fresh weight (FW).…”
Section: Methodsmentioning
confidence: 99%
“…The Bacillus spp. were isolated by serial dilution as described in our previous studies [ 37 , 38 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, some species belong to the same genus as our identified species were confirmed to have positive effect on plant growth. For instance, some species of Bacillus, Pseudomonas, Acremonium and Humicola could promote plant growth due to their antagonistic activity, the production of IAA or specific substance to activate resistance for control of diseases (Dharni et al 2014;Hassan et al 2015;Khabbaz et al 2015;Wenhsiung 2009;Yang et al 2014). On the other side, some species of these genera showed negative effect on plant growth due to their broadspectrum pathogenic activity (Elbanna et al 2014;Furuya et al 2005;Iakovleva et al 2013;Racedo et al 2013;Zhang et al 2014).…”
Section: Discussionmentioning
confidence: 99%